SOCIAL, CULTURAL AND PSYCHOLOGICAL FACTORS IN THE FORMATION OF HUMAN CAPITAL - Umida Qayumova, daughter of Mukhammadjon (Sciental Journals Publishing, 2025)
This article analyzes the theoretical foundations and structural composition of human capital, as well as the socioeconomic factors influencing its development. It comprehensively examines the key components of human capital: education, health, professional skills, sociocultural values, and psychological potential.
Keywords: Human capital, education, health, social factors, economic factor, innovative potential, psychological factor, emotional intelligence, behavior, personal development, social environment.